NGOPI: MEMAKNAI AKTIVITAS MINUM KOPI DALAM KONTEKS BUDAYA POPULER - Michael Bernhard Djami (Sekolah Tinggi Teologi Aletheia, 2020)
Ngopi or drinking coffee is an activity that many people do, from the young to the old, from students to office employees. But, ngopi or the activity of drinking coffee has experienced the development of meaning in popular culture. Ngopi is no longer interpreted as a consumptive activity only. Ngopi can also be interpreted as a productive activity as well as a spiritual activity. The meaning of ngopi as a consumptive and productive activity in this paper is inspired by the writing of F. X. Rudi Setiawan, entitled